Diatomic molecule catalysts toward synergistic electrocatalytic carbon dioxide reduction. Issue 12 (1st March 2023) - Hong, Liming; Liu, Xian; Chi, Baozhu; Xia, Guomin; Wang, Hongming
Abstract : The two adjacent Co atoms in the catalyst are 0.523 nm apart and could synergistically activate CO2 and H2 O to form a hydrogen bond. Synergistic catalysis could promote CO2 activation, stabilize the intermediate, and decrease the energy barrier. Abstract : Synergistic catalysis with diatomic catalysts is an effective means to boost carbon dioxide (CO2 ) electroreduction efficiency and product selectivity; studies in this field also contribute to an atomic-level understanding of the synergy mechanism. However, the precise design of atoms in diatomic active centers is extremely challenging. Herein, a diatomic-molecule catalyst (DMC), double Co-salophen (D-Co) with a precise Co–Co distance of 0.523 nm, was supported on carbon nanotubes using a non-covalent anchoring strategy. The catalyst exhibits excellent performance in the electrochemical CO2 reduction reaction (CO2 RR) with a CO faradaic efficiency of 91.76% at −0.70 V versus a reversible hydrogen electrode (RHE), a turnover frequency of 2056.7 h −1 at −0.90 V vs. RHE, and good stability. This excellent CO2 RR performance is attributed to the synergistic adsorption and activation of H2 O and CO2 molecules on both Co atomic sites, which are connected by strong hydrogen bonds. Density functional theory calculations demonstrate that this type of hydrogen bond promotes CO2 activation, stabilizes the intermediate, and decreases the energy barrier. The DMC developed in this study provides a new template and strategy for the precise and rational design and preparation of diatomic molecule catalysts.